Interacting with others while reacting to the environment. (7th July 2022) - Fischer, Ilan; Levin, Simon A.; Rubenstein, Daniel I.; Avrashi, Shacked; Givon, Lior; Oz, Tomer
Abstract: Here, we revise Pietraszewski's model of groups by assigning participant pairs with two triplets, denoting: (1) the type of game that models the interaction, (2) its critical switching point between alternatives (i.e., the game's similarity threshold), and (3) the perception of strategic similarity with the opponent. These triplets provide a set of primitives that accounts for individuals' strategic motivations and observed behaviors.